Physiological Aspects of Lipid Metabolism in the Arctic Zone of the Russian Federation (Review) - Veronika A. Solovyova; Ulker G. Guseynova; Nataliya V. Solovieva; Nikolay S. Ishekov; Andrey G. Soloviev; Lyubov I. Gubareva (Журнал медико-биологических исследований)
This article aimed to systematize data on lipid metabolism parameters in various population groups of the Arctic region in the historical aspect and in modern conditions. The materials were selected using international (Web of Science and Scopus) and Russian (Cyberleninka and eLIBRARY.RU) databases. The following keywords were searched for: Arctic, lipid metabolism, risk factors. The sample included 34 works on the changes in lipid metabolism in the inhabitants of the Arctic region published between 1979 and 2023. It has been shown that the indigenous population is more likely to have a favourable blood lipid profile, with a low content of lowdensity lipoproteins (LDL) and triglycerides (TG), but high content of high-density lipoproteins (HDL). In zerogeneration newcomers, when their adaptation is disrupted, atherogenic dyslipidaemia often develops, while in first- and second-generation newcomers, lipid metabolism occupies an intermediate position, approaching the parameters of the indigenous population. Along with climatic and geographical conditions, socio-economic factors (dietary changes, smoking and alcohol abuse) affect the human body, leading to atherogenic dyslipidaemia, which is the basis of cardiovascular diseases. An important role in assessing lipid metabolism disorders in the Arctic is played by determining more reliable markers of atherosclerosis, namely, the content of apolipoproteins (apoA and apoB) and fatty acids consumed. The indigenous inhabitants of the North typically have a protein- and fatrich diet characterized by increased levels of omega-3 and decreased levels of omega-6 polyunsaturated fatty acids (PUFAs). However, in recent decades, low levels of both omega-3 and omega-6 PUFAs have become more common. For early detection of signs of lipid metabolism disorders, we need to study not only the “traditional” parameters, i.e. total cholesterol, TG, LDL and HDL, but also apoA-I and apoB as well as omega-6 and omega-3 PUFAs in order to develop science-based diagnostic methods, differentiated wellness programmes and therapeutic measures.